Implementasi dan Evaluasi Konfigurasi Awal Sistem Operasi Ubuntu 26.04 LTS menggunakan Oracle VM VirtualBox - Effenia Fahreza Siregar; Muhammad Fachri Anshori; Harry Pradana; Rasya Febrian; Ibnu Fajar Ritonga; Abbas Fatiha; Firman Manik; Sahat Parulian Sitorus (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2026)
Abstract Operating Systems practicum requires a safe and flexible learning environment that enables students to perform operating system installation and configuration without affecting the host operating system. One of the approaches that can be implemented is the use of virtualization technology through Oracle VM VirtualBox. This study aims to implement Ubuntu 26.04 LTS using Oracle VM VirtualBox and evaluate the initial system configuration as a supporting medium for Operating Systems practicum. The research employed an implementation method with a descriptive approach. The research stages included literature review, hardware and software preparation, virtual machine creation, virtual hardware configuration, Ubuntu 26.04 LTS installation, initial system configuration, and implementation verification. The results indicate that the implementation process was successfully completed. Ubuntu 26.04 LTS was installed and operated successfully in a virtual environment, recognized the allocated virtual hardware resources, and functioned properly after the initial configuration. Furthermore, Oracle VM VirtualBox provided a secure, flexible, and easily configurable virtual environment without affecting the host operating system. Therefore, the implementation of Ubuntu 26.04 LTS using Oracle VM VirtualBox can serve as an effective alternative learning medium to support Operating Systems practicum.